A note from history: Landmarks in history of cancer, part 7. Issue 15 (14th April 2015) - Hajdu, Steven I.; Vadmal, Manjunath; Tang, Ping
<x xml:space="preserve">Abstract</x> In the 2 and half decades reviewed (1970‐1995), research established that chromosomal translocation, deletion, and DNA amplification are prerequisites to cancerogenesis and that oncogenes, tumor‐suppressor genes, growth factors, and cytokines play crucial roles in the pathomechanism of cancer. Human papillomavirus, human immunodeficiency virus, herpes virus, and hepatitis B virus were identified as cancer‐causing viruses. Several laboratory tests were developed for the detection of primary and recurrent cancers, and cancer prevention by screening methods was popularized. Sonography, computerized tomography, magnetic resonance imaging, positron emission tomography, excision of sentinel lymph nodes, and immunohistochemical techniques became routine procedures. Clinicopathologic staging and classification of tumors were standardized. Limited surgery, adjuvant and neoadjuvant chemoradiation, and the therapeutic use of monoclonal antibodies, tumor vaccines, and targeted chemotherapy became routine practice. The decline in cancer incidence and mortality demonstrated that cancer prevention and advancement in oncology are pivotal to success in the crusade against cancer. Above all, it was clearly established that the care of patients with cancer can be accomplished best in a multidisciplinary setting involving surgical oncologists, radiologists, radiation therapists, medical oncologists, surgical pathologists, and laboratory scientists. In conclusion, the 25 years from 1970 and 1995 are the high‐water mark in clinical oncology, and this is the period when oncology turned from art to science. Cancer 2015;121:2480–2513. © 2015 American Cancer Society.